6c+4c+3=

Simple and best practice solution for 6c+4c+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6c+4c+3= equation:


Simplifying
6c + 4c + 3 = 0

Reorder the terms:
3 + 6c + 4c = 0

Combine like terms: 6c + 4c = 10c
3 + 10c = 0

Solving
3 + 10c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 10c = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 10c = 0 + -3
10c = 0 + -3

Combine like terms: 0 + -3 = -3
10c = -3

Divide each side by '10'.
c = -0.3

Simplifying
c = -0.3

See similar equations:

| -6=b-2+1 | | -6r+3r=21 | | -1x-7=-9 | | 27-4=x | | -18=-8v-v | | 25=7-4x | | -8x^2+48x+576=0 | | 1=1-2x+5x | | 3n-2-4n=-2 | | 8x+12x=2200 | | 4x+8x=2200 | | 5/2c=35/3 | | -log(x+9)-log(x-9)=-2log | | -21=5x-5+4 | | -u/7=-25 | | X=y^2-10y-25 | | 8x-7-8x=4 | | 2x-16y=8 | | A+14=14 | | -12=5p+p | | (j-2)/2j | | 3(v+5)-10=-13 | | 2x+5=x-2.5 | | 3+2*6-4=32 | | 0=4.9x^2+4x-10 | | -6=p-4p | | 7.50x-3.50x+15=95 | | 3(w-8)=-33 | | -.5=cos(pi•t/6) | | 1/x-3/4=x/1 | | 49=6u-17 | | 4l-12=8+5l |

Equations solver categories